Improving resistance to lepidopteran pests and herbicide using Sanming dominant genic male sterile rice (Oryza sativa L.) - Li, Zhen; Liu, Xu; Zhang, Hua; Li, Pingbo; Yao, Fangyin (Frontiers in Plant Science, 2024)
In order to improve both the resistance to lepidopteran pests and resistance to herbicide imazethapyr of mainstay japonica varieties in Huang-Huai rice region, the Sanming dominant genic male sterile (S-DGMS) rice was used as a platform to facilitate the pyramiding of functional genes and the replacement of genomic background. Twelve novel lines were developed, each carrying a crystal toxin gene conferring resistance to lepidopteran pests and the allele ALS 627N conferring resistance to herbicide imazethapyr in the background of a mainstay japonica variety. Genomic background of twelve novel lines was examined using 48 specified molecular markers, and each line carried less than two polymorphic markers relative to the corresponding mainstay variety. All twelve lines displayed high resistance to lepidopteran pests and the herbicide imazethapyr. The major agronomic traits of twelve lines showed no difference relative to the responding mainstay variety under spraying of pesticide. The popularization of the twelve japonica lines could facilitate the reduced use of pesticide and highly efficient control of weed and weedy rice in the future, thus promoting the development of japonica rice production. Therefore, S-DGMS rice could be a powerful tool in genetic improvement of target traits in rice.